Some experiments on extreme masking - Kleczkowski, P. (Archives of Acoustics, 2006)
Some experiments are described, in which the structure of the information received by thehuman ear is made to be comparable to the structure of the information received by the eye.The appropriate processing of the acoustic signals is performed in the time-frequency plane.This operation can also be seen as an artificial, extreme masking, where there is only onemasker in each region of the time-frequency plane and all other sounds are entirely masked.The experiments were performed on audio signals. It was found that the ear perceives littledifference between the original sounds and the processed sounds.